2019
DOI: 10.5114/jcb.2019.85778
|View full text |Cite
|
Sign up to set email alerts
|

Single institution implementation of permanent 131Cs interstitial brachytherapy for previously irradiated patients with resectable recurrent head and neck carcinoma

Abstract: Purpose: Permanent interstitial brachytherapy is an appealing treatment modality for patients with locoregional recurrent, resectable head and neck carcinoma (HNC), having previously received radiation. Cesium-131 (131 Cs) is a permanent implant brachytherapy isotope, with a low average photon energy of 30 keV and a short half-life of 9.7 days. Exposure to medical staff and family members is low; patient isolation and patient room shielding are not required. This work presents a single institution's implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…They reported overall and progression-free survival at 18 months were 45 and 37% respectively, similar to our report at 58 and 33% respectively at 24 months. Bar-ad et al reported 15 patients treated with Cs-131 brachytherapy for re-irradiation after surgical resection (29). The mean implant dose was 56.1 Gy, with similar treatment implementation to our approach, though no toxicity or tumor control endpoints were reported.…”
Section: Discussionsupporting
confidence: 54%
“…They reported overall and progression-free survival at 18 months were 45 and 37% respectively, similar to our report at 58 and 33% respectively at 24 months. Bar-ad et al reported 15 patients treated with Cs-131 brachytherapy for re-irradiation after surgical resection (29). The mean implant dose was 56.1 Gy, with similar treatment implementation to our approach, though no toxicity or tumor control endpoints were reported.…”
Section: Discussionsupporting
confidence: 54%
“…Dosing is designed to be at 60 Gy at 0.5 to 1 cm from the surface of the seed. 1 If two different planes of seeds are required to contour the surgical defect, then they do not collapse on each other upon closure, which prevents radiation hot spots. 4 Once the 1 x 1 cm grid of seeds are established, the mesh or individual strands are secured with sutures or clips to the surrounding fascia (Supporting Video 1).…”
Section: Methodsmentioning
confidence: 99%
“…Cesium (Cs)-131 is a permanent implantable brachytherapy with a half-life of 9.7 days and average photon energy of 30 keV. 1 Compared to external beam radiation or high dose rate brachytherapy using Iridium-192, the lower energy photons from Cs-131 decay allow for more localized deposition of dose, decreasing the dose delivered to nearby tissues and potentially reducing treatment complications. 1 The feasibility of Cs-131 implants for recurrent head and neck cancer (HNC) has been demonstrated with acceptably low levels of exposure to staff during the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preplanning was completed by a head and neck cancer surgeon and radiation oncologist to determine the total area of risk to be covered, the prescribed radiation dose, the strength and number of the Cs-131 seeds, and the surrounding critical structures of concern. Cs-131 seeds were ordered prior to surgical resection (16). Source placement followed conventional planar implant techniques.…”
Section: Patient and Tumor Characteristicsmentioning
confidence: 99%